DAKWAH INKLUSIF DI KOTA PAREPARE - Iskandar Iskandar; Natsir Mahmud; Darussalam Syamsuddin; Usman Jasad (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2018)
The results of this dissertation research show (1) the orientations of the inclusive insightful da’wah materials in Kecamatan Bacukiki are that da'i must be sincere, that da'i becomesa role model, that da'i always learns and upgrades knowledge. Inclusive da'wah should use local languages, straightforward ways, narrative-substantive da’wah without indoctrination, calm and wise da'wah. Da’wah should be suitable to the needs of mad'u, suitable to the development of science and technology, and the level of knowledge of mad'u. Inclusive Da'wah is carried out based on da'wah maps andits relevance to plural societies. It should encourage social transformation, can be applied, and carried out in a dialogical manner; (2) The obstacles of inclusive da'wah are fanatical people, da'wah that does not enlighten and educate, da’wah that is not in accordance with the situation, conditions and ways of thinking of the people, da’wah that does not useBuginese language, preserved Buginese culture, da’i who are not yet competent, not communicative, and generally still low in IT skills; (3) The solutions to the obstacles of inclusive da'wah are that there should be a mapping of da'wah in Kecamatan Bacukiki, the Regional Government and Ministry of Religious Affairs must be synergistic, da’i should master the local language namely Buginese, da’i should be trained. Inclusive da'wah should be comprehensive, affordable access to the society, having syllabus, enlightening da'wah, and da’i who has competence, integrity and exemplary profile. The implications of this research are that (1) the Regional Government of Parepare must take care of the tolerance and harmony of the Bacukiki society, (2) the Ministry of Religious Affairs of Parepare makes a map of da'wah, trains da'i, compensates da'i, etc.; (3) the Indonesian Ulema Council becomes a representative forum for the people and carries out its main duties and functions; (4) Religious Social Organizations train their da'i professionally and responsibly; and (5) Da’wah practitioners always develop their competence and qualifications, master Arabic, Indonesian, and Buginese, master Information and Communication Technology, and protect them selves to have personality integrity.